REPRESENTASI FANATISME SUPPORTER DALAM FILM ROMEO DAN JULIET - Aditya Rizky Gunanto (Universitas Mercu Buana, 2015)
Romeo and Juliet movie tells the story of love between two mutually hostile angggota supporters. Rangga as a staunch supporter of Persija FC, and Dessy as a staunch supporter of Arsenal FC In unite their love, Rangga and Dessy faced with a problem, so they decided to get married and plan to escape to a neutral city where their competition is not a problem. But brother Dessy not bend over backwards to stop it. A true love story of two people has been the biggest supporter of the affairs of the two organizations .The theory used in this study is the theory of semiotics by Charles Sanders Peirce. Semiotics is the study of signs, meanings and proper functioning of the production of meaning. Charles Sanders Peirce's theory of meaning called triangle (triangle of meaning), including signs, objects (reference mark), and interpretant (users sign) This type of research uses descriptive qualitative approach. Research methods with semiotic analysis that focuses on the meaning of each sign in the form of an icon, index, and symbol. The unit of analysis is a picture of a sign in the movie